(untitled) (Al-Academy, 2024)
Music has a strong presence, despite its primitiveness, since the Greek times, through the religious rituals that were presented on the occasion of the Dionysian holidays, as well as the dithering songs, through some developments that took place according to the taste and legacies of Roman society, and then in the era of the Church and the Middle Ages, the arrival of the Renaissance in which musical concepts changed and their association with developments Theatrical drama, as this development influenced music to be an important element in the structure of theatrical performance and its form of artistic, aesthetic, intellectual and technical forms.Music has had an important impact on some theatrical trends until there is a dramatic form called musical theatre, as well as the operatic form or operetta, and there are also musical plays, as well as the technological development taking place in the mechanisms of shaping music to serve as sound effects that stimulate feelings and make them work within the fabric of the show. Theatrical, as well as the emergence of educational and psychological trends that employed theater for an educational purpose called the school theater, and based on that importance and its effects on the structure of theatrical performance and its dramatic space and its multiple functions in simulating theatrical action, as the research problem came through the following question: Is there an aesthetic and educational employment of music and sound effects In school theater performances? The researcher adopts the answer to this question, titled her research tagged (aesthetic and educational employment of music and sound effects in school theater performances), which is one of the renewable topics due to the renewal of the elements and techniques of theatrical presentation according to the technological developments taking place in the fields of music and theatre